2006
DOI: 10.1111/j.1468-3083.2006.01877.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of long‐term treatment with cyclosporin A for atopic dermatitis

Abstract: We conclude that CsA is an effective and safe treatment for patients with severe AD refractory to conventional treatment, provided that the recommended guidelines for its administration are strictly observed. However, in contrast to previous reports, we found that 8% (6/73) of patients experienced a rebound phenomenon after discontinuation of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 16 publications
(27 reference statements)
3
69
5
Order By: Relevance
“…These results suggest there is a relationship between long-term CsA treatment and a prolonged remission period for AD. Overall, the adverse events in this study were relatively milder and smaller in number than those in other studies by Hijnen et al 6 and Garcia-Bustinduy et al 13 . In the report of Hijnen et al 6 , the initially used doses of CsA varied up to 5 mg/kg.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…These results suggest there is a relationship between long-term CsA treatment and a prolonged remission period for AD. Overall, the adverse events in this study were relatively milder and smaller in number than those in other studies by Hijnen et al 6 and Garcia-Bustinduy et al 13 . In the report of Hijnen et al 6 , the initially used doses of CsA varied up to 5 mg/kg.…”
Section: Discussioncontrasting
confidence: 51%
“…Overall, the adverse events in this study were relatively milder and smaller in number than those in other studies by Hijnen et al 6 and Garcia-Bustinduy et al 13 . In the report of Hijnen et al 6 , the initially used doses of CsA varied up to 5 mg/kg. An increased serum creatinine level more than 30% above the baseline value was observed in 7 patients (9.6 %).…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Classically, CsA has been used as an immunosuppressive agent in organ transplantation in humans and cats [2,3,12,36]. Recently, CsA has been reported as an effective drug for the long-term management of pruritus in human and canine atopic dermatitis (AD) [10,11,22,30]. In addition, several clinical trials have revealed that CsA is also effective for controlling pruritus in feline skin diseases [21,34].…”
mentioning
confidence: 99%